Enteral nutrition before bowel preparation improves the safety of colonoscopy in the elderly - Jianfeng YAO; Wei ZHANG; Jie CHEN; Gansheng ZHANG; Songbai ZHENG (Turkish Journal of Gastroenterology, 2019)
-